Bioavailability Enhancement of Poorly Water-soluble Nano Diosgenin by Encapsulation using Chitosan/Bovine Serum Albumin Bilayers - Pathak, S. R. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: To enhance the bioavailability of poorly water-soluble diosgenin (DG) by chitosan/BSA encapsulated nanoparticle formulation. Material and Methods: 0.1% chitosan aqueous solution was mixed with freshly prepared saturated DG solution followed by probe-sonication for 30 min., thereafter 0.1% BSA solution was added drop-wise and sonicated for another layer formation. Procedure was repeated for bilayer formation. After each layer formation nanoparticles were centrifuged and resuspended in fresh DI water. Results and Discussion: The DLS of nanosized DG shown to have a radius of 2 nm to 40 nm. Surface morphology of nanoDG has been observed using SEM. Non-significant changes under the UV/Vis and IR, suggest the retention of drug properties at nano level. Chitosan/BSA coatings generated a higher surface charge (ca. +28 mV and -30mV) resulting in good colloidal stability. Dissolution technique was used for release profiling of drug from layer-by-layer assembly. Conclusion: The combination of biocompatible ionic polymers chitosan/BSA bilayer encapsulation around nanoDG, allowed sustained release of drug molecule up to 30 hours.